2019
DOI: 10.2174/1570159x16666180628164432
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Serotonin: Complexity of Interactions and Implications for Epileptic Seizures and Epileptogenesis

Abstract: A burgeoning literature documents the confluence of ovarian steroids and central serotonergic systems in the injuction of epileptic seizures and epileptogenesis. Estrogen administration in animals reduces neuronal death from seizures by up regulation of the prosurvival molecule i.e. Bcl-2, anti-oxidant potential and protection of NPY interneurons. Serotonin modulates epileptiform activity in either direction i.e administration of 5-HT agonists or reuptake inhibitors leads to activation of 5-HT3 and 5-HT1A rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 191 publications
(176 reference statements)
1
18
0
Order By: Relevance
“…Serotonin may be implicated in the regulation of seizures, but whether or not it can potentiate the effects of epileptogenic factors has not been fully established. Animal studies have shown that both an increase and decrease of brain serotonin may decrease the threshold for seizures [13,14,22]. Females had higher serotonin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin may be implicated in the regulation of seizures, but whether or not it can potentiate the effects of epileptogenic factors has not been fully established. Animal studies have shown that both an increase and decrease of brain serotonin may decrease the threshold for seizures [13,14,22]. Females had higher serotonin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Low serotonin levels do not cross the BBB, but high levels are shown to cause BBB breakdown [13]. While low levels of serotonin decrease the threshold for seizures [14], high levels, such as during an overdose of selective serotonin reuptake inhibitors, are known to cause 'serotonin syndrome', which is characterized by seizures and muscle wasting, features also observed in OAE [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are available in which the authors point to antiepileptic, and even neuroprotective, effects of estrogen. The hormone decreases neuronal death during seizures through up-regulation of the prosurvival molecule-Bcl-2, anti-oxidant potential as well as protection of NPY interneurons (82). In addition, it was demonstrated that the examined steroids caused "the induction of dendritic spine proliferation on serotonin neurons thus thawing a profound effect on serotonergic transmission" by the activation of 5-HT3 and 5-HT1A receptors (82).…”
Section: Neurosteroids and Catamenial Epilepsymentioning
confidence: 99%
“…The case is more difficult to prove with estrogen, because this hormone displays both pro- ( 79 81 ) and anticonvulsant properties ( 82 ), its mechanisms of actions being not fully understood. It is suspected that estrogen works through intracellular estrogen receptors, ER-alpha and ER-beta, which are found in nuclei of some neurons, e.g.…”
Section: Neurosteroids and Catamenial Epilepsymentioning
confidence: 99%
“…Recently, gold nanoparticles are emerging as unique, efficient, simple and reliable solutions for scientific and technical challenges of existing processes, machines or systems in various disciplines of engineering sciences . Discovery of new drugs or pharmaceutical combinations for the treatment of many life threating complex clinical conditions such as opportunistic infections, delayed wound healing, MDR (Multidrug resistance) bacterial and cancerous diseases, as well as epilepsy; not only required suitability and rationality in approaches and their selection but also proven to be time consuming exercise at the cost of exploiting limited and valuable resources in bulk . Most of the conventional nanoparticles and catalytic reactions facing limited success in term of efficiency of reaction yield as well as requires strict controlling of desired conditions .…”
Section: Introductionmentioning
confidence: 99%